TERAPI KELOMPOK MENGGUNAKAN TEKNIK MINDFULNESS GUNA MENURUNKAN TINGKAT STRES PADA SISWA KELAS X SMKN X BATANG - Nabilah, Igriya Fauzi (Psikologi Prima, 2024)
Stress is an individual response to a stressor or trigger. Almost every individual has experienced a stressful condition or a certain pressure; the only difference is the trigger or stressor that causes it and the severity of the stress condition. In this study, seven grade X students experienced stress at one of the SMK N Batang; the causes of stress experienced by the students were different; some were caused by parental problems, demands from the family, inability to participate in learning, or being a victim of parental problems. The assessment conducted on these seven students used observation, interview, and psychological testing approaches. Based on the assessment results show that seven students experienced stress with different levels of severity using the DASS or Depression Anxiety Stress Scale test as a form of pretest before being given the intervention. The intervention in this study is to use mindfulness techniques to reduce the level of stress experienced by students. After the intervention process is given, the participants are seen again for their stress scores by giving a post-test. The post-test results showed a p-value of 0.018, and if the p-coefficient value is less than 0.05 or (p < 0.05), then it shows that the stress experienced by the participants is reduced with the provision of Mindfulness therapy.